Affected persons in business rescue proceedings : has a balance been struck? - Zwane, Muziwakhe Simphiwe (Department of Commercial Law, 2015)
The Companies Act of 2008 (the Act) has revolutionised the corporate law landscape in South Africa. The Act has been drafted with the specific intention of promoting access to the economy and of ensuring that cumbersome and costly procedures are (to a large extent) a thing of the past. These objects are a necessity when striving to ensure that South Africa's alarming inequality is abated. One of the central features of the 2008 Act is the introduction of business rescue, a procedure which represents a blatant attempt at striving to preserve ailing companies. The Act states that one of the main objects with regards to business rescue is ensuring that the procedure balances the competing interests involved. The purpose of this thesis therefore is to consider to what extent the 2008 Act has been able to achieve this. This will be done by analysing the rights given to employees, shareholders and creditors. This thesis will argue that though the procedure is a step in the right direction, it has failed to strike a proper balance by overly empowering employees and conversely leaving shareholders somewhat impotent. This thesis will also argue that some of the mechanisms employed, though they may be admirable in what they strive to achieve, leave far too much doubt as to their practicality. The overall conclusion reached is that a major overhaul is not required in order to rid this much needed procedure of its flaws.